Urbanisation effect on dengue cases in Hulu Langat, Selangor (2014-2018) - Mohd Tohit, Nor Faiza; Ramli, Lina Farhana; Salleh, Rosilawati; Suli, Zaliza; H, M. Nasir; Husam, Abdullah (Malaysian Medical Association, 2019)
INTRODUCTION: The frequency and magnitude of epidemic disease continued to increase in tandem with rapid urbanisation. Mosquitoes carrying the dengue virus can increase following unplanned and unhealthy urbanisation. In the large urban regions, crowded human populations live in intimate association with equally large mosquito populations provides the ideal home for maintenance of the viruses and the periodic generation of epidemic strains. METHODS: Data from e-Dengue registry including the urban sub-districts, between 2014 to 2018 were reviewed. Descriptive analysis was conducted to examine the epidemiology of Dengue fever in the urban regions of Hulu Langat district, Selangor which consist of Kajang, Cheras and Ampang sub-districts. RESULTS: Total incidence rate of Dengue in urban sub-districts in year 2014 was 1,060 per 100,000 populations (n=10,254) while in year 2018 the incidence decreased to 691 per 100,000 populations (n=6,762). Most of the cases were contributed by sub-district Kajang (43%) and Ampang (23%). Meanwhile the cases were mostly recorded from premises of landed houses (61%) and strata (21.1%). Case-fatality rate was increasing in trend from year 2014 to 2017 (0.18% to 0.22%) however noted to decrease in 2018 with 0.15%. Most of the death were from Kajang sub-district (37%), followed by Ampang (36%). DISCUSSION: Dense population in urban regions contributed to Dengue hyperendemicity in Hulu Langat. Orchestrated holistic approach in controlling Dengue outbreak in urban regions must be conducted wisely.